The Effect of Laser Radiation in Different Mordant and Ratios on Silk Fabrics Dyed with Weld (Reseda luteola L.) - PARS, ABDULKADİR; SANCAK, ERHAN; ÖZEN, MUSTAFA SABRİ (TAYLOR & FRANCIS INC, 2022)
In this study, the silk fabrics mordanted at the ratio of 1%, 5%, 10%, 20% of aluminum potassium sulfate (KAl(SO4)(2)center dot 12H(2)O) and 0.1%, 0.5%, 1%, 3%, of iron sulfate (FeSO4) were separately dyed 50% weld (Reseda luteola L.). Then firstly, laser radiation was used on un-mordanted silk fabrics and as a second step, silk samples with different ratios mordanted and dyed with weld were irradiated to investigate the laser radiation effects on color using several combinations of the two main laser parameters namely energy density and number of pulses. Nd:YAG laser device was used two different wavelengths of 1064 nm and 532 nm, and it was found that the laser wavelength of 532 nm is most appropriate to all dyed fabrics, while 1064 nm wavelength causes damages such as discoloration and burning in the iron sulfate mordanted fabrics. Colorimetric analysis was performed to examine surface alterations of silk samples. The CIEL*a*b* color values of the silk fabrics were measured and compared with each other. In general, the use of iron sulfate (FeSO4) as a mordant increased the color difference (Delta E*) of dyed fabrics at 1064 nm. The color coordinates and fastness values of rubbing and light were investigated. Morphological analysis was performed using optical and scanning electron microscopy. Elemental analysis was performed using SEM-EDX (scanning electron microscopy-energy-dispersive X-ray spectroscopy) to identify mordants. A reserved phase high-performance liquid chromatography (RP-HPLC) with the diode-array detection (DAD) method was utilized for the identification of the components of dyes present in the silk samples.
Keywords: Laser; radiation; weld; HPLC; CIEL*a*b*; SEM-EDX; NATURAL DYES; DYEING PROPERTIES; WALLOON OAK; COMPLEXES; ALUMINUM(III); IRRADIATION; FLAVONOIDS